Direito, sociedade e representação: uma análise sistêmica acerca das audiências públicas sobre meio ambiente e a complexidade de participação social na suprema corte brasileira - Maia, Selmar José (Universidade do Vale do Rio dos Sinos, 2018)
The following research focuses on the importance of Brazilian participatory Democracy and on the communicative denunciation of social movements through the public hearings held in the Federal Supreme Court in cases of great public interest and of notable general repercussion. Furthermore, it highlights the importance of social movements for Democracy as a systemic irritation of the Judiciary power. It should be noted that the present work proposes an analysis based on the pragmatic-systemic matrix, evidencing, above all, the complexity of the subjects treated and the importance of observing who are the experts that have access to the legal procedures in the Brazilian Supreme Court. Finally, as a case study, a comparative analysis is proposed on the public hearings regarding Environmental Law, more specifically on the subjects related to: import of used tires, burning of sugarcane, prohibition on the use of asbestos and Brazilian New Forest Code, addressing who were the participants of these events and what forms the main arguments invoked in the Brazilian Supreme Court to legitimize or repeal the current law.
Keywords: Democracia participativa; Movimentos sociais; Teoria dos Sistemas; Supremo Tribunal Federal; Audiência Pública; Participative Democracy; Social movements; System Theory; Brazilian Federal Court of Justice; Public Hearing; ACCNPQ::Ciências Sociais Aplicadas::Direito